Superstructures: Enzyme‐Driven Hasselback‐Like DNA‐Based Inorganic Superstructures (Adv. Funct. Mater. 45/2017). (1st December 2017) - Lee, Jae Sung; Kim, Hyejin; Jo, Changshin; Jeong, Jaepil; Ko, Jeonghyun; Han, Sangwoo; Lee, Min Sun; Lee, Ho‐Young; Han, Jeong Woo; Lee, Jinwoo; Lee, Jong Bum
Abstract : The enzymatic synthesis of DNA‐based inorganic micro/nanostructures is described by Jong Bum Lee and co‐workers in article number1704213 . DNA‐inorganic hybrid superstructures are grown using a continuous enzymatic feeding system. In contrast to current synthetic techniques, precise control over morphologies, components and functionalities is achieved. This approach is highly apt for various interdisciplinary and biomedical applications, including contrast agents and electrode materials.